Професор Костянтин Олексійович Зворикін – один із фундаторів науки з технології матеріалів - Гутник, Марина Валеріївна (Запорізький національний університет, 2018)
Розкрито основні напрями та результати діяльності одного із фундаторів науки з технології матеріалів – Костянтина Олексійовича Зворикіна. Встановлено, що наукові інтереси ученого були доволі різноманітними – дослідження з технології деревини та борошномельного виробництва, кораблебудування, опору металів. Випускник Санкт-Петербурзького технологічного інституту пов’язав своє наукове життя з Харківським практичним технологічним інститутом, де став першим професором механічної технології та Київським політехнічним інститутом, де став першим деканом механічного відділення та згодом і директором.

Industry in the southeast of Ukraine after the abolition of serfdom began to develop rapidly. There were very few specialists in the country who were able to prepare future engineers-mechanics and who had thorough knowledge of materials. Among such scientists is Professor Konstantin Zworykin. The article deals with the engineering and design activities by K. Zworykin in 1885 – 1888. His formation as a leading scientist in the field of mechanical technology at Kharkiv Practical Institute of Technology (KhPTI) is determined. Data about publications by K. Zworykin are given. In particular, he wrote the fundamental monograph «The Work and the Efforts are needed to Separate Mechanical shavings», it was published in 1893. Investigations by the scientist became innovative for those time, received a lot of positive reviews. Next year another work by K. Zworykin – «The Course of flour-grinding production» was published. This tutorial has become classic in this field. It was shown that in 1894 he was appointed as a professor of mechanical technology of KhPTI. At the invitation of the first director of the Kiev Polytechnic Institute (KPI) Professor V. Kirpichev in 1898 K. Zworykin became the first dean of the mechanical department of the newly established institution. From June 1904 to August 1905 he was the director of the KPI. The reasons for such a short stay in this capacity are disclosed. During 1905–1917 he was engaged in scientific and educational activities in Kharkiv. The subjects of his scientific works are shown. From 1918 to 1926, he worked at the KPI. Since 1922 he headed the research department of mechanical technology. The information about his advisory work for the military is given. The scientist died in 1928 and was buried in Lukyanovsk cemetery. So Professor K. Zworykin is one of the leading researchers in the field of mechanical engineering at Kharkiv Practical Institute of Technology and Kyiv Polytechnic Institute.
Professor Konstantin Zworykin is one of the founders of the materials technology science
Keywords: Зворикін К. О.; ректор; вчений; Харківський практичний технологічний інститут; механіка прикладна; суднобудування; виробництво борошномельне; технологія деревини; Zworykin K.; Kharkiv practical institute of technology; rector; applied mechanics; shipbuilding; flour-milling; wood technology